Mechanisms and measurements of sialidase in pneumonia - Coetzee, Carla (Department of Chemistry, 2025)
Streptococcus pneumonia is a major human pathogen that resides in the upper airway and nasopharynx. It colonizes asymptomatically but can spread to other regions in the host body causing diseases such as bacteremia, otitis media and meningitis. This pathogen has evolved to evade the host-immune response and make individuals susceptible to reinfection by encoding three enzymes: NanA, NanB and NanC where NanA is the focus of this study. NanA cleaves 3'- sialyllactose or 6'-sialyllactosefound on the host cell walls to release N-acetylneuraminic acid (sialic acid) and lactose. This aids the bacterial adhesion which contributes to the overall virulence of the pathogen. Thus, one aim of the pharmaceutical industry is to design and develop inhibitors for these enzymes. However, for any inhibitor screening (to evaluate the potency of a potential drug) certain kinetic constants are required that can only be obtained doing biological enzymatic assays. A prerequisite of these assays is to either have a detectable substrate or product via a spectroscopic method (e.g. fluorescence) to monitor the rate of the reaction. Neither 3'-sialyllactose,6'-sialyllactose nor their products display intrinsic fluorescence and only have absorbance. Unfortunately, the signals are often weak and broad and so it is not a sensible method for detection. An artificial substrate, 2'-(4-Methylumbelliferyl)-α-D-N acetylneuraminic acid (MUANA) is cleaved by NanA to produce sialic acid and 4- methylumbelliferone (4-MU). MUANA was introduced to mimic the natural 3'-sialyllactose and 6'-sialyllactose as 4-MU (unlike sialic acid or lactose) is fluorescent. However, there is still the question as to how valid MUANA is in replacing either 3'-sialyllactose or 6'-sialyllactose. To answer this question, an enzyme kinetic experiment was conducted using MUANA to obtain kinetic constants. These constants were then compared to those of a modified assay using 3'- sialyllactose and 6'-sialyllactose as substrates. The constants differed across the two assays; thus, an inhibition screening was performed to test the potency of four commercial drugs against NanA using both the MUANA and 3'-sialyllactose. The inhibition constants agreed extremely well for the two most potent inhibitors but deviated slightly for the lowest ranked two. The inhibitors were ranked from most potent to least potent in the order of Oseltamivir, DANA, Zanamivir and Peramivir. Two in-silico methods were used to verify the experimental results: molecular modelling and molecular docking. Molecular modelling was used to calculate the free energy of the reaction between NanA and MUANA and to compare to the free energy obtained by the experimental data. However, only one of the two required mechanistic steps could be simulated. Molecular docking is a virtual tool used to assess the binding affinity (potency) of a molecule, and thus was used to calculate a score to rank the inhibitors' potency. The in-silico approach yielded the same order as the experimental results. Thus, MUANA is a suitable replacement for the 3'-sialyllactose and 6'-sialyllactose.